2016
DOI: 10.1111/1471-0528.14180
|View full text |Cite
|
Sign up to set email alerts
|

Psychological morbidity associated with hyperemesis gravidarum: a systematic review and meta‐analysis

Abstract: Background Psychological illness occurring in association with hyperemesis gravidarum (HG) has been widely reported.Objective To determine if there is a higher incidence of psychological morbidity in women with HG compared with women without significant nausea and vomiting in pregnancy.Search strategy PubMed, MEDLINE, Embase and PsychINFO were searched up to September 2015.Selection criteria Articles referring to psychological morbidity in relation to HG. For meta-analysis case-control studies using numerical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(78 citation statements)
references
References 57 publications
(240 reference statements)
5
73
0
Order By: Relevance
“…As yet, no single tool is validated for holistically assessing women’s symptoms, however questioning can seek to understand how symptoms are affecting quality of life, the economic burden,1516 and psychosocial effects 67. The Quality of Life question on the PUQE score does not directly contribute to the score, but helps to provides a holistic assessment of the impact of symptoms on women, particularly for women experiencing profound nausea without vomiting or retching, and it has been validated to correspond inversely with the PUQE score 13…”
Section: How Do You Diagnose and Assess Severity Of Hg?mentioning
confidence: 99%
See 3 more Smart Citations
“…As yet, no single tool is validated for holistically assessing women’s symptoms, however questioning can seek to understand how symptoms are affecting quality of life, the economic burden,1516 and psychosocial effects 67. The Quality of Life question on the PUQE score does not directly contribute to the score, but helps to provides a holistic assessment of the impact of symptoms on women, particularly for women experiencing profound nausea without vomiting or retching, and it has been validated to correspond inversely with the PUQE score 13…”
Section: How Do You Diagnose and Assess Severity Of Hg?mentioning
confidence: 99%
“…HG can have profound psychosocial consequences 67. Negative psychological effects of NVP and HG include loss of identity, social isolation, feelings of guilt and suicidal ideation,7 and pressure to terminate the pregnancy 33.…”
Section: What Are the Risks?mentioning
confidence: 99%
See 2 more Smart Citations
“…A recent meta-analysis by Mitchell-Jones et al, reported a relationship between HG and depression and anxiety in pregnancy. Mitchell-Jones et al, concluded that their meta-analysis demonstrated an increase in psychological morbidity in women with HG (6). It has been reported in some studies that depression risk enhanced in HG patients with a history of depression (7,8), however, on the contrary, it has been reported in some studies that depression risk enhanced in HG patients with Copyright (9,10).…”
Section: Introductionmentioning
confidence: 99%